Proses Komunikasi PT Garuda Branch Office Padang Dalam Sosialisasi Protokol Kesehatan Di Lingkungan Kerja - Bening Setara Bulan (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
The communication process when implementing new normal can be interpreted as the sequence of events that occur when an individual conveys a message to another individual about implementing new habits in the middle of the work environment. New normal is a change in behaviors or habits to keep carrying out activities as usual but by always applying health protocols in the midst of the COVID-19 pandemic. The new habits areto use a mask, social distancing, always wash hands and avoid crowds. In the communication process, socialization is needed as a first step to introduce new normal policies. Socialization is done by people, groups, intitutions, who teach others things that must be known in order to become new guidelines. Socialization about the new normal is a form of solution for the efforts of the employees from PT Garuda to be wiser in implementing the new normal health protocol, also be able to develop curiosity and comply with the enactment of new work regulations. The current COVID-19 pandemic requires every company to be more active in socialization and preventive health measures to protect the employees from the COVID-19 transmission chain. In this study, researcher used five informants which were divided into key informats, consisting of general managers, marketing & sales executives, Garuda Branch Office Padang ticketing, and supporting informants, consisting of OB and security. The method used in this study is a qualitative method with Laswell‘s approach theory. The results of this study is that the communication process in the application of new normal un the work environment using WA media groups and email blast and supported by interpersonal communication to all employees.